Risk factors for subsequent febrile seizures in the FEBSTAT study. (6th June 2016) - Hesdorffer, Dale C.; Shinnar, Shlomo; Lax, Daniel N.; Pellock, John M.; Nordli, Douglas R.; Seinfeld, Syndi; Gallentine, William; Frank, L. Matthew; Lewis, Darrell V.; Shinnar, Ruth C.; Bello, Jacqueline A.; Chan, Stephen; et al.
Summary: Objectives: To identify risk and risk factors for developing a subsequent febrile seizure (FS) in children with a first febrile status epilepticus (FSE) compared to a first simple febrile seizure (SFS). To identify home use of rescue medications for subsequent FS. Methods: Cases included a first FS that was FSE drawn from FEBSTAT and Columbia cohorts. Controls were a first SFS. Cases and controls were classified according to established FEBSTAT protocols. Cumulative risk for subsequent FS over a 5‐year period was compared in FSE versus SFS, and Cox proportional hazards regression was conducted. Separate analysis examined subsequent FS within FSE. The use of rescue medications at home was assessed for subsequent FS. Results: Risk for a subsequent FSE was significantly increased in FSE versus SFS. Any magnetic resonance imaging (MRI) abnormality increased the risk 3.4‐fold (p < 0.05), adjusting for age at first FS and FSE and in analyses restricted to children whose first FS was FSE (any MRI abnormality hazard ratio [HR] 2.9, p < 0.05). The risk for a second FS of any type or of subsequent FS lasting >10 min over the 5‐year follow‐up did not differ in FSE versus SFS. Rectal diazepam was administered at home to 5 (23.8%) of 21 children with subsequent FS lasting ≥10 min. Significance: Compared to controls, FSE was associated with an increased risk for subsequent FSE, suggesting the propensity of children with an initial prolonged seizure to experience a prolonged recurrence. Any baseline MRI abnormality increased the recurrence risk when FSE was compared to SFS and when FSE was studied alone. A minority of children with a subsequent FS lasting 10 min or longer were treated with rectal diazepam at home, despite receiving prescriptions after the first FSE. This indicates the need to further improve the education of clinicians and parents in order to prevent subsequent FSE.